Kebijakan Pengembangan Kurikulum PAI di MTs AL-Fathaniyah Kota Serang - Masitoh, Itoh; Wasehudin, Wasehudin; Hilmiyati, Fitri; Muslihah, Eneng (Kopertais Wilayah I DKI Jakarta dan Banten, 2024)
Today the curriculum is a special and interesting subject to research and develop, because the curriculum is used as a guide in implementing the learning process in educational institutions, especially in madrasas related to the PAI curriculum. The purpose of this research is to describe the PAI Curriculum Development policy and its implementation at MTs Al-Fathaniyah Serang City. Qualitative research with document collection techniques, observation, interviews. The techniques include data reduction, data display, inference and verification. The results of the research are that the policy for developing the PAI curriculum at MTs Al-Fathaniyah Serang City is based on a legal hierarchy, namely from the 1945 Constitution; UU no. 20 of 2003 concerning SISDIKNAS; and KMA Number 183 of 2019 concerning PAI Curriculum and Arabic Language in Madrasas. In implementing the 2019 KMA 183 policy in developing the PAI curriculum at MTs Al-Fathaniyah, when viewed in terms of the fields of study in KMA 183, there are additional subjects, namely Nahwu and QQWT Sciences. As well as in other developments, namely developing and improving the RPP syllabus starting from KI, KD listed on the KMA and then developing it into several learning indicators adapted to the KKO from Bloom's Taxonomy. Also in the implementation of learning using various methods, models and varied strategies. After that, an evaluation was held to find out how far the PAI curriculum was developed at MTs Al-Fathaniyah.